Consumer Perspective on Food Pairing Low-Sugar Rich in Antioxidant Tea Ponds Supplemented with Apple Vinegar - Olivia Feny; Yohana Sutiknyawati Kusuma Dewi; Lucky Hartanti (Publikasi Indonesia, 2024)
The purpose of this study was to compare the physicochemical and sensory results of apple cider vinegar supplementation with various concentrations on low-sugar liang tea and to obtain information on complementary foods in consuming low-sugar liang tea as the best food pairing. This study was designed using a randomized group design. consisting of 5 treatments with 5 repetitions with the addition of apple cider vinegar treatment consisting of 5 levels a0 0 % (control), a1 0,5 %, a2 1 % ,a3 1,5 %, a4 2 % The results of the food pairing analysis were carried out descriptively .0% treatment was declared as the best treatment with physicochemical values pH 5.71 , TPT 7.28 °brix, color L 34.02, color a 2.52, color b 3.88, and color sensory value 4.07 (like ), Aroma 4.20 (like), acidity level 3.83( rather like), and overall acceptance 4.13 (like). In food pairing, the highest percentage chosen by respondents was fried bananas (28.6%) from 49 respondents. Comparison of the physicochemical and sensory characteristics of low-sugar apple cider vinegar supplementation had differences in each parameter, namely pH, TPT, and the color parameter had no significant differences. Whereas the color sensory parameters had no significantly different results, while the sensory parameters of aroma, acidity level, and overall acceptance had significantly different results for each treatment